Green Accounting In Village-Owned Business Entities Using Environmental Accounting - Abdul Manap1; Mohammad Djauhari; Muhammad Yasin; Ikhwan Ikhwan; Adnedi Adnedi (STIE AMKOP, 2023)
The process of finding, recognising, measuring, presenting, and disclosing all corporate expenditures made to enhance environmental quality by preventing, mitigating, and even avoiding negative environmental impacts is known as